2020
DOI: 10.1507/endocrj.ej19-0278
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a clinical model to predict intraoperative hemodynamic instability in patients with pheochromocytomas surgery

Abstract: Although currently the primary strategy for the treatment of pheochromocytomas is surgery, it is associated with a high risk of intraoperative hemodynamic instability (IHD), even with adequate preoperative medical preparation, which may result in life-threatening situations. The aim of this study was to develop and validate a nomogram for preoperative prediction of IHD related to pheochromocytoma surgery. The development cohort consisted of 283 patients with pheochromocytoma who underwent unilateral laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Sixty-seven additional articles were excluded after full-text evaluation. The remaining 14 articles were subjected to systematic review [ 4 , 5 , 6 , 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and nine of those articles were meta-analyzed [ 4 , 6 , 7 , 17 , 19 , 21 , 22 , 23 , 24 ]. We detailed the study selection process in a flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-seven additional articles were excluded after full-text evaluation. The remaining 14 articles were subjected to systematic review [ 4 , 5 , 6 , 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and nine of those articles were meta-analyzed [ 4 , 6 , 7 , 17 , 19 , 21 , 22 , 23 , 24 ]. We detailed the study selection process in a flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Surgical procedure (open surgery) [ 4 ], retroperitoneal approach [ 20 ], pre-operative beta blockade therapy [ 25 ], clinical symptoms [ 5 ], plasma epinephrine [ 7 ], plasma norepinephrine [ 7 ], plasma dopamine [ 7 ], plasma normetanephrine [ 25 ], urinary metanephrine and/or normetanephrine [ 5 ], familial disease [ 17 ], and the use of crystal/colloid fluid [ 23 ] were significantly associated with perioperative hemodynamic instability in one study each. Additionally, urinary epinephrine was evaluated in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much attention has been paid to intraoperative haemodynamic instability in patients with PCC/PGLs. [2][3][4][5] Only a few studies have focused on the predictors of postoperative hypotension that require continuous vasopressor support. Postoperative hypotension is associated with an increased risk of myocardial injury, acute kidney injury, stroke and even death.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective data have suggested that preoperative volume expansion achieved by saline infusion or increased water intake can reduce the risk of postural hypotension and perioperative hypotension by optimizing intravascular status [4][5][6][7]. Bai and colleagues [8] developed a nomogram for preoperative prediction of intraoperative hemodynamic instability (IHD) related to surgical treatment of pheochromocytoma. They found that an absence of preoperative volume expansion was an effective predictor for IHD involvement.…”
Section: Introductionmentioning
confidence: 99%